2021
DOI: 10.1111/imb.12691
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysis triggering hormone is essential for larva–pupa–adult transformation in Leptinotarsa decemlineata

Abstract: In Drosophila melanogaster, ecdysis triggering hormone (ETH) is the key factor triggering ecdysis behaviour and promoting trachea clearance. However, whether ETH plays the dual roles in non‐dipteran insects is unknown. In this survey, we found that Ldeth mRNA levels were positively correlated with circulating 20‐hydroxyecdysone (20E) titers in Leptinotarsa decemlineata. Ingestion of an ecdysteroid agonist halofenozide or 20E stimulated the transcription of Ldeth, whereas RNA interference (RNAi) of ecdysteroido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…In insects such as Leptinotarsa decemlineata and Bactrocera dorsalis, ETH is mainly produced by Inka epithelial cells of the endotracheal gland in the trachea. The ETH expression level is the highest at the late premolt stage (Shi et al, 2017;Shen et al, 2021). In Drosophila, EH is expressed in the neuronal tissues and trachea, which participate in the regulation of molting behaviors (Scott et al, 2020).…”
Section: Transcripts Of Ecdysis Triggering Hormone Eclosion Hormone A...mentioning
confidence: 99%
See 2 more Smart Citations
“…In insects such as Leptinotarsa decemlineata and Bactrocera dorsalis, ETH is mainly produced by Inka epithelial cells of the endotracheal gland in the trachea. The ETH expression level is the highest at the late premolt stage (Shi et al, 2017;Shen et al, 2021). In Drosophila, EH is expressed in the neuronal tissues and trachea, which participate in the regulation of molting behaviors (Scott et al, 2020).…”
Section: Transcripts Of Ecdysis Triggering Hormone Eclosion Hormone A...mentioning
confidence: 99%
“…Even the initiation of the molting process has started, there is no guarantee that the animal will molt successfully as the fulfillment of the subsequent events must be straightly followed. In insects, neuropeptides that induce molting behavior include ecdysis-triggering hormone (ETH) (Shi et al, 2019a;Minh Nhut et al, 2020;Shen et al, 2021), eclosion hormone (EH) (Hull et al, 2009;Zhou et al, 2017;Scott et al, 2020), crustacean cardioactive peptide (CCAP) (Veelaert et al, 1997;Arakane et al, 2008;Jackson et al, 2009), etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All dsRNAs were generated by Escherichia coli HT115 (DE3) competent cells lacking RNase III following the established method. 10,11 The bacterial solutions (at a dsRNA concentration of about 0.5 μg/mL) were used for the experiment.…”
Section: Preparation Of Dsrnasmentioning
confidence: 99%
“…Researchers have found that ETH has additional roles besides initiating ecdysis. In insects, ETH plays dual roles, initiation of ecdysis and trachea clearance ( 11 , 12 ). In Drosophila , the knockdown of ecdysis triggering hormone receptor ( ETHR ) revealed differential expression of genes involved in axon guidance, courtship behavior, and chemosensory functions, which indicated a role in the regulation of courtship behavior ( 13 ).…”
Section: Introductionmentioning
confidence: 99%